IDDAH BAGI WANITA KHULU' DAN IMPLIKASI HUKUMNYA DALAM PERSPEKTIF HUKUM ISLAM - Mohammad Hifni; Yuli Astuti (Res Justitia : Jurnal Ilmu Hukum, 2023)
Living in divorce as found in the interpretation of as-Sabuni, that living is interpreted as mut'ah, which means the giving of a husband to his divorced wife, be it in the form of money, clothing or any provision as a favor and respect for his wife and avoiding the cruelty of the thalaq he dropped. In Islamic Law that the criteria for an ex-wife who is entitled to a living from her ex-husband, also only as long as the wife carries out the iddah period, because during the iddah period the husband's marriage relationship is still ongoing, because thalaq raj'i does not abolish the marriage contract, does not eliminate the husband's rights to his wife, nor the wife's rights to her husband. Meanwhile, women who are not entitled to a living from their ex-husbands are such as: women who do khulu', women whose husbands die, women who wait for their iddah period because of fasakh, and after divorce an ex-wife only earns a living only during the iddah period